Modeling Solar Converters for Harmonic and Resonance Studies - M. Pielahn; K. Mudunkotuwa; Dharshana Muthumuni (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
Solar and renewable plants are increasingly being added to national grids. One technical drawback of renewable generators is that they tend to cause a significant harmonic distortion of the current and voltage waveforms. The harmonic distortions are amplified when the natural resonances of the grid interact with the injected harmonics from the power electronic based PV generation. A sustained harmonic distortion can lead to equipment failure, reduced plant output or a complete plant shutdown. Therefore, it is important to study harmonic interactions and resonance issues using fully detailed EMT models before the commissioning of a renewable plant. This paper outlines important features of modelling solar converters for the use of harmonic and resonance studies.